PENGUATAN ELECTORAL JUSTICE SYSTEM PADA BAWASLU MENGHADAPI PEMILU SERENTAK 2024 - Abdullah (Bawaslu Provinsi Jawa Barat, 2021)
Faced with challenges and the potential for greater vulnerability than previous elections in Indonesia's democratic history, the country is preparing for simultaneous general elections in 2024. To ensure that the 2024 General Election is held with legitimacy and integrity, an accurate, systematic, and comprehensive strategy regarding the electoral justice system is required. As a result, it is deemed necessary to conduct an analysis of the concept of the electoral justice system at the General Elections Supervisory Agency (Bawaslu), as well as an analysis of strategies for strengthening the electoral justice system in preparation for the 2024 General Election. Preventing violations, supervising the election process, resolving disputes, and prosecuting violators are the primary responsibilities. The General Supervisory Agency (Bawaslu) institution's task is an important part of the electoral justice system, particularly in the effort to hold elections with integrity and justice.